(untitled) (Polis (Santiago), 2018)
The author of this text asserts that men and women are equal since they both share the same inherent and infinite potential. True spirituality implies self knowledge, and consists in the realization of the power of life and of love that exists potentially in all of us. It is necessary to overcome all forms of discrimination towards women. The author encourages women to fight for their rights, because they are asleep and must awake, change their mind, and rediscover and value that they represent the basic spiritual principle: universal motherhood. She must become free of the prejudices of patriarcal society, not only for themselves, but because all present societies need to develop the feminine values contained in such principle: love, strength, delicacy, patience and tolerance. Peace will not be possible if harmony among the masculin and feminine which resides inside each person is not re-established. Only thus it will become possible to overcome competitivity and hatred, which rule the existing world.